Exposure to negative stereotypes impairs older adults' self-control. Issue 2 (4th March 2019) - Alquist, Jessica L.; Price, Mindi M.; Hancock, David; Talley, Amelia E.; Cukrowicz, Kelly
Abstract: The present studies were designed to test the hypothesis that exposure to negative stereotypes about older adults impairs older adults' self-control as measured with a delay discounting task. Participants (ages 65–77) were assigned to read either a positive or negative article on the cognitive effects of aging (Study 1 and 2) or were assigned to a neutral control condition (Study 2). Older adults in the negative article condition chose delayed rewards less frequently than older adults in the positive or neutral conditions. Follow up tests suggested that the difference between positive and negative article conditions was mediated by participants' discrepancy between their chronological and subjective age. Negative stereotypes about older adults may impair older adults' ability to resist immediate impulses in order to pursue their goals.